Perencanaan Strategik Sistem Dan Teknologi Informasi Pada Sekolah Dasar Islam Alfauzien Depok Menggunakan Metode Ward & Peppard - julizal julizal; Puput Irfansyah (LPPM, 2018)
Abstract. Islamic Elementary School (SD Islam) is one part of the educational environment in which to do training and development of students toward the achievement of educational goals. Therefore, the implementation must have a plan which redirected, clear objectives and implementation of reliable.“Strategic Planning Systems and Information Technology at the Islamic Elementary School Alfauzien Depok environment